Pelatihan Digital Marketing Berbasis Platform Shopee dalam Menumbuhkan Jiwa Kewirausahaan Mahasiswa - Muhammad Sofwan; Risdalina Risdalina; Suci Hayati; Destrinelli Destrinelli; Ahmad Syarif; Indryani Indryani; Bahera Bahera (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
This community service program aimed to foster students’ entrepreneurial spirit through digital marketing training based on the Shopee platform in Jambi Province. The underlying problem of this activity was the tendency of students to use digital platforms primarily for consumptive purposes, particularly online shopping, rather than as a medium for entrepreneurship. The method employed in this program was an applicative training approach, which included an introduction to Shopee as an online marketing platform as well as hands-on practice in opening an online store, adding products, and promoting products. The evaluation of the program was conducted using a participant satisfaction questionnaire. The results showed that students provided positive responses to the training activities. Participants perceived the training as relevant to their needs, easy to understand, and beneficial in enhancing their understanding and interest in entrepreneurship. Therefore, Shopee-based digital marketing training was considered effective in fostering students’ entrepreneurial spirit and encouraging the productive use of digital platforms.